2010
DOI: 10.1089/hum.2009.128
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Lung and Liver After Intravenous Infusion of Polyethylenimine Complexes of Sleeping Beauty Transposons

Abstract: Two methods of systemic gene delivery have been extensively explored, using the mouse as a model system: hydrodynamic delivery, wherein a DNA solution equivalent in volume to 10% of the mouse weight is injected intravenously in less than 10 sec, and condensation of DNA with polyethylenimine (PEI) for standard intravenous infusion. Our goal in this study was to evaluate quantitatively the kinetics of gene expression, using these two methods for delivery of Sleeping Beauty transposons. Transposons carrying a luc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…Condensation of the SB plasmids with polyethylenimine or encapsulation in nanocapsules for standard intravenous infusion may be an interesting alternative to deliver the transgene into the liver. 40,41 A second issue regarding the clinical use of the SB transposon system is the safety of SB-mediated integration. It has been shown that SB has no preference for integration into transcription units and transcriptional regulatory regions and that the majority of insertions that do occur in genes are located in introns.…”
Section: Discussionmentioning
confidence: 99%
“…Condensation of the SB plasmids with polyethylenimine or encapsulation in nanocapsules for standard intravenous infusion may be an interesting alternative to deliver the transgene into the liver. 40,41 A second issue regarding the clinical use of the SB transposon system is the safety of SB-mediated integration. It has been shown that SB has no preference for integration into transcription units and transcriptional regulatory regions and that the majority of insertions that do occur in genes are located in introns.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, PEI transfection has been explored as an alternative to HD in order to mediate in vivo transposon delivery through intravenous infusion into mice but was at least 100-fold less efficient compared to HD delivery. 167 Recently, in vivo administration of nanoparticles carrying transposons has emerged as an efficient method to deliver transgenes into circulating T cells in mice, and in situ engineered T cells exhibited similar activity to conventional engineered T cells generated by ex vivo gene transfer. 168 Nanoparticles represents a potentially attractive technology to deliver transposons into liver sinusoidal endothelial cells.…”
Section: Hscmentioning
confidence: 99%
“…Previous studies demonstrated significant liver tropism of PLLand PEI-based cationic polymers in biodistribution studies [36,37]. To gain insight on the mobility of HmT-PCION complex in vivo, IVIS whole-body luciferase assays were performed to track the movement of HmT-PCION in a MCF7 tumor-bearing mouse model after treatment with PBS with MGF, HmT with MGF, or HmT-PCION with or without MGF (Fig.…”
Section: Enhanced Therapeutic Efficacy Of Oncolytic Ad-pcion Complex mentioning
confidence: 99%